Flupirtine derivatives as potential treatment for the neuronal ceroid lipofuscinoses. Issue 9 (14th August 2018) - Makoukji, Joelle; Saadeh, Fadi; Mansour, Karl Albert; El‐Sitt, Sally; Al Ali, Jamal; Kinarivala, Nihar; Trippier, Paul C.; Boustany, Rose‐Mary
Abstract: Objective: Neuronal Ceroid Lipofuscinoses (NCL) are fatal inherited neurodegenerative diseases with established neuronal cell death and increased ceramide levels in brain, hence, a need for disease‐modifying drug candidates, with potential to enhance growth, reduce apoptosis and lower ceramide in neuronal precursor PC12 cells and human NCL cell lines using enhanced flupirtine aromatic carbamate derivatives in vitro. Methods: Aromatic carbamate derivatives were tested by establishing growth curves under pro‐apoptotic conditions and activity evaluated by trypan blue and JC‐1 staining, as well as a drop in pro‐apoptotic ceramide in neuronal precursor PC12 cells following siRNA knockdown of the CLN3 gene, and CLN1‐/CLN2‐/CLN3‐/CLN6‐/CLN8 patient‐derived lymphoblasts. Ceramide levels were determined in CLN1‐/CLN2‐/CLN3‐/CLN6‐/CLN8 patient‐derived lymphoblasts before and after treatment. Expression of BCL‐2, ceramide synthesis enzymes ( CERS2/CERS6/SMPD1/DEGS2 ) and Caspases 3/8/9 levels were compared in treated versus untreated CLN3‐deficient PC12 cells by qRT‐PCR. Results: Retigabine, the benzyl‐derivatized carbamate and an allyl carbamate derivative were neuroprotective in CLN3‐defective PC12 cells and rescued CLN1‐/CLN2‐/CLN3‐/CLN6‐/CLN8 patient‐derived lymphoblasts from diminished growth and accelerated apoptosis. All drugs decreased ceramide in CLN1‐/CLN2‐/CLN3‐/CLN6‐/CLN8 patient‐derived lymphoblasts. Increased BCL‐2 and decreased ceramide synthesis enzyme expression were established in CLN3‐derived PC12 cells treated with the benzyl and allyl carbamate derivatives. They down‐regulated Caspase 3/Caspase 8 expression. Caspase 9 expression was reduced by the benzyl‐derivatized carbamate. Interpretation: These findings establish that compounds analogous to flupirtine demonstrate anti‐apoptotic activity with potential for treatment of NCL disease and use of ceramide as a marker for these diseases.